Memaknai Konsep Hemat sebagai Tindakan Rasional Berorientasi Nilai pada Masyarakat Desa Kelayu - Juita Hikmatul Ulya; M. Zainul Asror; Muh. Ridwan Markarma (SIWAYANG Journal: Publikasi Ilmiah Bidang Pariwisata, Kebudayaan, dan Antropologi, 2026)
Frugality is a socio-economic practice that involves not only resource management and expenditure control but also reflects values, norms, habits, and meanings socially constructed within community life. This study aims to examine how the people of Kelayu Village, Selong District, interpret frugality in their everyday lives and how this value is constructed through economic practices, family relationships, and socio-cultural contexts. The study employs a qualitative approach informed by economic sociology and Max Weber’s concept of value-rational social action (wertrational). Data were collected through observation, in-depth interviews, and documentation, and analyzed through data reduction, data display, conclusion drawing, and source and technique triangulation. The findings show that frugality is constructed through three interconnected domains: the meaning of the home as a form of material sufficiency, household financial management based on spending priorities, and the intergenerational transmission of frugality through parental example and habituation. The findings indicate that frugality is not merely a response to economic constraints but, under certain conditions, represents a value-oriented social practice grounded in simplicity, sufficiency, usefulness, and the avoidance of waste. This study contributes to economic sociology by demonstrating that economic rationality can be embedded in social relations and cultural values within the everyday household practices of a local community.